Disease management in horticulture crops through microbial interventions: An overview - BORA, POPY; BORA, L C (The Indian Journal of Agricultural Sciences, 2020)
Horticultural crops-based nutritional security is now a buzz word to Indian agriculture. Significant level of progress has been made towards the management of some pandemic pathogens affecting the production economics of horticultural crops. Some of these pathogens are : Fusarium oxysporum, Ralstonia solanacearum, Pythium spp., Phytophthora spp, Xanthomonas spp., Colletotrichum spp., Pencillium spp , Alternaria spp etc. Many soil-borne diseases as well as post harvest fungi are effectively addressed through a variety of bioagents belonging to predominant microbial genera represented by Trichoderma spp., Bacillus spp., Gliocadium spp. and fluorescent Pseudomonads. Our thumping success with different microbial bioformulations showed an effective control of both pests and diseases in major crops of northeast India comprising tea, banana, turmeric, ginger, in addition to bacterial wilt of Bhoot jolokia, tomato, hydroponic lettuce and Rhizoctonia- induced root rot management of chilli and patchouli. These area wide and crop wide results put forth a renewed claim in favour of developing a vibrant organic horticulture in years to come. All these issues are analysed highlighting the future use of rhizospheric and endophytic plant beneficial microbes as dominant communities.